VD_FINDINFO HC / 2016 / 930 vom 22. September 2016 - VD Tribunal cantonal (2016)
OBLIGATION D'ENTRETIEN, MAJORITÉ{ÂGE}, MODIFICATION DES CIRCONSTANCES, FORMATION PROFESSIONNELLE | 277 al. 2 CC, 286 al. 2 CC